Pengaruh Pemberian Unripe Banana Flour (Pisang Berlin) terhadap Aktivitas Fisik pada Tikus Putih Wistar Jantan Model Dislipidemia - Hendra Hermawan; Ayu Febriyatna; Ratih Putri Damayati; Firda Agustin (Politeknik Negeri Jember, 2020)
Dyslipidemia is a risk factors for non communicable diseases. The emergence of disease means that a person does not have prime physical fitness which can have a negative impact, namely experiencing limitations on physical activity One way to increase the physical activity of people with dyslipidemia is by giving belin banana flour. Bananas are believed to be able to increase physical activity due to the high energy content of 90 ccal/100 grams of banana berlin. The purpose of this study was to determine the effect of giving unripe banana flour (Banana Berlin) on physical activity in white rats (Rattus Norvergicus L) wistar dyslipidemia strain. This type of research is true-experimental with pretest-posttestt with control group. This study used 18 male wistar rats with a body weight of 150-200 grams aged 2-3 month. Rats were divided into 2 control group and 1 treatment group given unrip banana flour (UBF) at a dose of 0,144 g/head/day for 30 days. Physical activity is measured by swimming. Date were analyzed using the One Way Anova test, the Post Hoc or Mann Whitney test, and the paired T-test was carried out with the result that there was a significant difference in the physical activity of the rats before the intervention (p=0,003), there was a significant difference in the physical activity of the rats after the intervention (p=0,000), and there was a significant difference in the physical activity of the rats before and after the intervention (p= 0,003). Giving unripe banana flour (UBF) can not be said to ble able to increased physcal activity because the control group can not be used to be standard group